Numerical Analysis of Beams and Frames with Strain-Softening Materials - Łodygowski, T. (Engineering Transactions, 1988)
The present study shows the softening post-peak deflection behaviour of beams and frames for cracking reinforced concrete materials. The layered finite elements are used in the analysis. Concrete exhibits strain-softening effects in tension and compression and the steel reinforcement is assumed to be elastic-plastic. The bond slip of reinforcement is neglected but still it is shown that the model satisfactorily approximates the existing experimental tests. The arc-length method which seems to be very general even for snap-through and snap-back structural behaviour, is used in numerical analysis.